2004
DOI: 10.1029/2003gl018591
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity and anisotropy of seismic attenuation in the inner core

Abstract: [1] We evaluate seismic attenuation in the inner core from the spectral ratio between the seismic phase PKP(DF ) and either PKP(AB) or PKP(BC ) at the epicentral distances from 150°to 170°. The global data set is divided into two groups according to the position of the turning point of PKP(DF ) either in the eastern (from 50°E to 120°W) or the western hemisphere. In the eastern hemisphere the parameter t 8 shows strong dependence on the epicentral distance and no dependence on the angle between the Earth's spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 23 publications
(39 reference statements)
4
36
0
Order By: Relevance
“…Observations tell us that the inner core is seismically anisotropic, with P wave velocities ∼3% faster along the polar axis than in the equatorial plane (Creager, 1992;Song and Helmberger, 1993;Song, 1997;Song and Xu, 2002;Sun and Song, 2002;Beghein and Trampert, 2003;Oreshin and Vinnik, 2004). This would suggest that some of the crystals that make up the inner core have aligned in such a way that, overall, the seismically fast direction through the crystal aggregate is oriented along the polar axis of the Earth.…”
Section: Summary Statementsmentioning
confidence: 99%
“…Observations tell us that the inner core is seismically anisotropic, with P wave velocities ∼3% faster along the polar axis than in the equatorial plane (Creager, 1992;Song and Helmberger, 1993;Song, 1997;Song and Xu, 2002;Sun and Song, 2002;Beghein and Trampert, 2003;Oreshin and Vinnik, 2004). This would suggest that some of the crystals that make up the inner core have aligned in such a way that, overall, the seismically fast direction through the crystal aggregate is oriented along the polar axis of the Earth.…”
Section: Summary Statementsmentioning
confidence: 99%
“…Studies have shown evidence of anisotropy, oriented with the fast direction aligned to Earth's rotation axis (Poupinet et al, 1983;Morelli et al, 1986;Woodhouse et al, 1986;Creager, 1992;Vinnik et al, 1994;Irving and Deuss, 2011). A distinct east-west asymmetry has also been observed in the inner core, whereby the west hemisphere has lower velocity, weaker attenuation and stronger anisotropy than the east (Tanaka and Hamaguchi, 1997;Niu and Wen, 2001;Cao and Romanowicz, 2004;Oreshin and Vinnik, 2004;Deuss et al, 2010;. The difference in isotropic velocity between the hemispheres has been found to be between 0.5% (Sun and Song, 2008) and 1.5% (Garcia, 2002), with most studies finding a value of 0.8%-1% (Tanaka and Hamaguchi, 1997;Niu and Wen, 2001;Cao and Romanowicz, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Early studies using either of these techniques (Morelli et al, 1986;Woodhouse et al, 1986;Creager, 1992) proposed that the seismic velocity anisotropy in the inner core was both laterally invariant and depth-independent and that the axis of cylindrical anisotropy is aligned with Earth's rotation axis. More recent body wave studies have built up a picture of an inner core with a degree one 'hemispherical' structure (Tanaka & Hamaguchi, 1997;Creager, 1999;Oreshin & Vinnik, 2004) and a distinct innermost inner core where the anisotropy axis is at an angle of 45 • to the anisotropy axis in the rest of the inner core (Ishii & Dziewonski, 2002;Cormier & Stroujkova, 2005;Cao & Romanowicz, 2007;Sun & Song, 2008).…”
Section: Introductionmentioning
confidence: 99%